An Overview of Concept Hyponymy in Persian: From Cognitive Perspective (Dhaka University Journal of Linguistics, 2011)
In this paper the author is concerned with the role of cognitive and mental abilities of humans in the formation of hyponymy sense relation at the level of words of Persian language, additionally the importance of the role of developed image schemas in accordance with hyponymy, and also the function of some cognitive and analytical factors in the formation of these image schemas such as construal, consists of perspective (focus point and reference point), profile and scanning are so important to the author. The starting point is the study of the way of the formation of developed image schemas related to hyponymy sense relation. The author's fundamental claim is that the mentioned cognitive and analytical factors have a significant role in the formation of three developed image schemas related to hyponymy, and the mentioned schemas are given different names and they are shown through various figures as well. Next the theory of layered schemas (LST) is provided by analyzing some Persian simple structures including hyponymy. Moreover, we move towards a cognitive inter-lexical semantics in this paper by applying the proposed theory of the author (LST) on Persian linguistic data. For this purpose one example of Persian including hyponymy is analyzed on the basis of (LST). As the last step, the different stages of the formation of hyponymy sense relation between the words of Persian are shown through some cognitive figures to add a kind of consistency and support to the author's proposed program in this paper.Keywords: hyponymy; developed image schemas; cognitive inter-lexical semantics; layered schemas theoryDOI: 10.3329/dujl.v2i4.6897Dhaka University Journal of Linguistics Vol.2(4) August 2009 pp.1-18